2021
DOI: 10.46542/pe.2021.211.105120
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy education, workforce, practice, and sciences in Lebanon: Benchmarking with the FIP Development Goals

Abstract: Background: In 2020, the International Pharmaceutical Federation (FIP) published a set of 21 global development goals (DGs) that bring together workforce/education [W], practice [P], and science [S] in a transformative framework, defining an improved and more advanced pharmacy profession for the next decade. This paper aims to benchmark the context of the Lebanese pharmacy profession with the respective elements of the FIP DGs to optimise the previously suggested strategic plan. Methods: A group of pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Moreover, despite comprehensive, evidence-based strategic plans, including surveys and epidemiological research, previously developed and endorsed by the OPL, none has yet been implemented by health authorities, such as the MOPH [ 27 ]. Existing projects should be implemented in the short term; policies and regulations regarding pharmacy curricula reforms, accreditation, post-graduate training, recognition of pharmacy specialties, organizing the profession, and assessing advanced competencies should all be updated and applied [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite comprehensive, evidence-based strategic plans, including surveys and epidemiological research, previously developed and endorsed by the OPL, none has yet been implemented by health authorities, such as the MOPH [ 27 ]. Existing projects should be implemented in the short term; policies and regulations regarding pharmacy curricula reforms, accreditation, post-graduate training, recognition of pharmacy specialties, organizing the profession, and assessing advanced competencies should all be updated and applied [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed GAP analysis was later conducted for pharmacy education, workforce, practice, and sciences, through a benchmarking exercise with the FIP 2020 Development Goals that bring together workforce/education [W], practice [P], and science [S] in a transformative framework [ 22 ]. The cited document stated that in the short term, projects already developed by the OPL and suggested to the relevant authorities should be implemented immediately, e.g., pharmacy curricula reforms based on updated accreditation standards, the recognition of postgraduate training and pharmacy specialties, the organization of pharmacy education and practice, and the assessment of advanced competencies in different pharmacy areas.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, complementary aspects related to research and practice have already been tackled. In the medium term, a national research strategy was recommended, including early-career scientists, mentoring, and validation of assessment tools [ 22 ]. A recently developed Pharmaceutical Research Strategy was suggested subsequently [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main objective was to discuss how FDGs aim to increase the integration of pharmaceutical sciences, practice, and education globally. On top of that, it aimed to highlight how pharmacy students and young pharmacists/pharmaceutical scientists can take part with FIP to affect the outcomes of the FIP Development Goals, as well as to discuss how to increase the applicability of these goals (Sacre et al, 2021). (Fitzgerald, Pinto & Kos, 2007).…”
Section: Collaborations With Fipmentioning
confidence: 99%